Variação na quantidade de área florestal em unidades de conservação no Estado do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The disordered use of soil in protected areas can consequently lead to deforestation of these spaces, and tools such as geotechnologies have shown themselves, in different researches, to be an important ally to evaluate and monitor the use and transformations of the soil. The objective of this work is to identify and give total visibility of the forest area, in ha, that were suppressed or added in the territories of the state conservation units of Integral Protection and Sustainable Use in Pará, counting on the database of the Annual Mapping Project of the Land Use and Coverage in Brazil (MapBiomas), which aims to generate data and maps that help monitor land use and land cover. To obtain the information from the tool, the Amazon biome was selected, as well as only the State-level Conservation Units, making a temporal cut between the years 1985 to 2020, the data presented in that project are obtained through Satellite images Landsat 5, 7 and 8. The Utinga State Park Conservation Unit, of the Integral Protection group, was the one that presented the greatest loss of forest area during the studied period, equivalent to (5,508 ha), and the Monte Alegre State Park had the greatest increment, about (134 ha). In the Sustainable Use group, the Environmental Protection Area Triunfo do Xingu Conservation Unit was the one that presented the greatest loss of forest area equivalent to (323,833 ha), and the Trombetas State Forest Conservation Unit, was the one that presented the greatest increase, com (2,322 ha).
Keywords: MapBiomas; Unidades de conservação; Área florestal; CNPQ:: Ciências Biológicas